Discoveries in the Arctic Sea 1913 - 1914 and 1917 - 1918 / positions deduced and mapped by the Geodetic Survey of Canada - Geodetic Survey of Canada (1943)
Shows routes of Leffingwell-Mikkelsen, R.A. Bartlett, S.T. Storkerson Relief shown by hachures and spot heights. Deptsh shown by soundings Base map: "Arctic Coast of Alaska C & GS 9400" from the US Coast and Geodetic Survey Fold out map removed from: "The Friendly Arctic : the story of five years in polar regions" by Vilhjalmur Stefansson, 1943 Grayscale not given